(3QSGdI aj GdeYGO GdLSeGfjs - (3CMeO Hf SdjeGf Hf ceGd HGTG GdQhej , TeS GdOjf,J (B940 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO agPg QSGdI ai HjGf GdeYGO GdMSjeGfi hJaUjd eG hbY ajg ef GdNdGa Hjf GdSda bGd GdCeOi ai CHcGQ GdCacGQ PgHJ GdadGSaI s
(3BNQgG (B:s
(3hgPG eSJMjd HGdHOjgI ShGA cGf GdbHdjI PGJjI hjYhO hLhO GdTF HYOeG RGd Yfg hESJMGdJg ZjQ XGgQI hgd GdeTGLQI GdCajI JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B133 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B238 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B141s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeOQSI GdCMeOjI (B_ (3GdehUd (B(115) s
Keywords: (3GdeLGejYs